To Solution of Ecological Problems in Power Systems - A. M. Gashimov; G. J. Guseinov; K. B. Gurbanov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper analyses a possibility to minimize damage due to operation of power systems using fossil fuels. Technological schemes of purification processes ensuring efficient  solution of  the ecological problem, particularly, in the case of power station operating on natural gas and fuel oil  are proposed in the paper. The paper contains an analysis of the mechanism in respect of processes occurring in the proposed methods for gas and liquid purification against detrimental impurities.